Glycerol Utilization as Substrate for Ethanol Production in Escherichia coli Recombinant under an Aerobic Condition - Wahyu Suradi Pranata; Prayoga Suryadarma; Djumali Mangunwidjaja (Journal of Tropical Life Science, 2018)
The utilization of glycerol as a substrate for ethanol production in E. coli recombinant harboring ethanologenic gens (PDC and ADHB) under aerobic conditions was investigated. This research was conducted by using E. coli BW25113 which compared the growth characteristics on glycerol and glucose as carbon source. E. coli can grow well on both substrates and it consumed glycerol faster than glucose. On glucose, E. coli occurred overflow metabolism that indicated by high acetate accumulation. Meanwhile, on substrate of glycerol the acetate accumulation could be reduced. Using glycerol substrate on E. coli increased piruvate accumulation, comparing with glucose. Therefore, the growth characteristic of glycerol was more effective. In E. coli âˆ†pta/pHfdh/pTadhB-pdc utilized glycerol substrate was able to accumulate pyruvate as intermediate metabolite for produce 2.18 gL-1 ethanol.